Métodos de evaluación de los mallines patagónicos: Botanal y Pasturómetro - Buono, Gustavo Gabriel; Utrilla, Victor Ricardo; Nakamatsu, Viviana Beatriz; Villa, Martin Diego (Ediciones INTA, 2021)
Capítulo de libro.